House of sugar, house of stone: poems - Pérez, Emily, author; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2016)
These poems are suggested by themes and characters found in Grimm's Fairy Tales.
Keywords: Kinder- und Hausmärchen -- Poetry; Fairy tales -- Poetry